Providing culturally appropriate service for Muslim Americans: a perspective of social service providers. Issue 3 (4th May 2021) - Weng, Suzie S.; Davidson, Sarah; Kim, Mimi E.
ABSTRACT: This paper aims to acknowledge essential matters to be taken under consideration when working with Muslim Americans in social services in an effort to provide culturally appropriate services and promote social justice. Interviews were conducted with service providers who identify themselves as formerly or currently Muslim and have previously or are currently working with Muslim Americans. The themes found were: 1) oppression, discrimination, and stereotypes; 2) consequences for social work; 3) help-seeking; and 4) providing culturally appropriate services. Recognition of service workers' insider perspectives of working with Muslims will offer further insight on providing culturally appropriate services.